Recent Advances in Remote Sensing for Crop Growth Monitoring (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
This special issue book gathers sixteen papers focusing on the application of remote sensing techniques to crop growth monitoring. The studies feature multi-scale and multi-source remotely sensed data, a combination of empirical and physical approaches, and a range of topics on crop growth parameters estimation and crop mapping. It is recommended to graduate students, professors, scientists and engineers who have broad interests in the agricultural applications of remote sensing.